2004
DOI: 10.1038/sj.bjc.6601545
|View full text |Cite
|
Sign up to set email alerts
|

The −174 G/C gene polymorphism in interleukin-6 is associated with an aggressive breast cancer phenotype

Abstract: Serum and tissue levels of interleukin-6 (IL-6) have been implicated in the biological phenotype of breast carcinoma. A common G/C polymorphism at position À174 of the IL-6 promoter can influence the expression level of this gene. We therefore investigated for associations between this polymorphism and various phenotypic features in a series of 256 breast cancers. Individuals who were homozygous for the C allele (n ¼ 55) were more likely to have higher-grade tumours (P ¼ 0.039) with ductal histology (P ¼ 0.030… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 20 publications
(38 reference statements)
2
31
2
Order By: Relevance
“…As previously published for other malignancies (29), the À174 G/C IL6 polymorphism likely is important for carcinogenesis. Previously published data are conflicting (34,35). We cannot confirm data on the association between the IL6 polymorphism and clinicopathologic variables.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…As previously published for other malignancies (29), the À174 G/C IL6 polymorphism likely is important for carcinogenesis. Previously published data are conflicting (34,35). We cannot confirm data on the association between the IL6 polymorphism and clinicopathologic variables.…”
Section: Discussioncontrasting
confidence: 49%
“…DeMichele et al reported that the presence of the IL6 polymorphism was associated with an improved outcome in high-risk breast cancer (33), whereas Iacopetta et al showed that the IL6 polymorphism was predictive of an aggressive breast cancer phenotype (34).…”
mentioning
confidence: 99%
“…Gonzalez-Zuloeta et al (35) reported a nonsignificant 24% increased risk of breast cancer with IL6 in a nested case-control analysis in the Rotterdam Study. Two studies that have reported associations with survival after diagnosis with breast cancer have contradictory results with regard to the direction of effect of the C allele (36,37). Unfortunately, little is known about functionality of haplotypes, and we can only hypothesize that the function of the haplotype that includes multiple SNPs is similar in action to the functional SNPs within it.…”
Section: Discussionmentioning
confidence: 97%
“…Singlenucleotide polymorphisms in the IL-6 promoter, particularly the 2174 G/C polymorphism, have been associated with an aggressive breast cancer phenotype 47 and with breast cancer susceptibility and prognosis. 48 For example, inflammatory breast cancer has a higher metastatic potential than noninflammatory breast cancer.…”
Section: Breast Cancermentioning
confidence: 99%